The social life of the caftan in eighteenth-century Russia. Issue 3 (1st December 2016) - Ivleva, Victoria
This article explores the 'cultural biography' of the caftan, a garment, which underwent significant changes as a part of Peter I's urban clothing revolution. The article discusses the evolution of the caftan and changes in its functions and meanings, its historical, social and literary modes of circulation and the semiotic value it acquired in the eighteenth-century clothing system, and more broadly in eighteenth-century Russian culture. As a key garment of the Petrine dress reforms, the caftan became a material symbol of eighteenth-century modernizing processes and was often employed by writers to comment on social and cultural policies and practices. When the caftan (as part of a uniform) started to be associated with state control and the infringement on individual freedom, it was replaced by the dressing gown, which became a symbol of internal peace, freedom and creativity in literature and cultural life.